Transnational Taiwan - Pendery, David. author. aut Link
XI, 149 p. 2 illus.
Keywords: This book is a study of transnationalism, focusing on experience of migrants, immigrants, travelers, expatriates, aliens, evacuees, refugees, and nomad in the world, broadly, and Taiwan, particularly. Offering an entirely new framework for what Taiwan as a contested transnational space means for Asia—a heterotopia, in which multiple visions of politics and society can flourish—Dr. Pendery's refreshing vision offers insights for scholars of greater China, international relations, and the economics of the region. Pendery establishes a dialog and debate in the book pitting Samuel P. Huntington, Stephen Toulmin, and Edward W. Said, broadly examining their views of these ideas and issues. David Pendery grew up in Albuquerque, New Mexico, moving to San Francisco in 1984, and obtaining his B.A. in International Relations at San Francisco State University. He received an M.S. in Journalism at Boston University. He relocated to Taipei, Taiwan in 2000, andobtained his Ph.D. in English literature at National Chengchi University in Taipei. He is currently an Associate Professor in the Department of Applied Foreign Languages at National Taipei University of Business. He is married to a Taiwanese woman, and they have a five-year-old daughter.